Integrated Reverse Engineering Strategy for Large-Scale Mechanical Systems: Application to a Steam Turbine Rotor - Arailopoulos, Alexandros; Giagopoulos, Dimitrios; Zacharakis, Ilias; Pipili, Eleni (Frontiers in Built Environment, 2018)
An integrated reverse engineering methodology is proposed for a large-scale fully operational steam turbine rotor, considering issues related to the development of the CAD and FE model and the application of robust and effective computational finite element model updating techniques based on experimental modal analysis procedures. First, using an integrated reverse engineering strategy, the digital shape of the three sections of a steam turbine rotor was developed and the final parametric CAD model was created. The finite element model of the turbine was developed using tetrahedral solid elements. Due to complex geometry of the structure, the developed model consists of about fifty-five million DOFs. The identification of modal characteristics of the frame is based on acceleration time histories, which are obtained through an experimental investigation of its dynamic response in a support-free state by imposing impulsive loading. Experimentally identified modal modes and modal frequencies compared to the FE model predicted ones constitute the actual measure of fit. CMA-ES optimization algorithm is then implemented in order to finely tune material parameters, such as modulus of elasticity and density, in order to best match experi-mental and numerical data. Direct comparison of the numerical and experimental data verified the reliability and accuracy of the methodology applied. The identified finite element model is repre-sentative of the initial structural condition of the turbine and is used to develop a simplified finite element model, which then used for the turbine rotordynamic analysis. Accumulated knowledge of the dynamic behavior of the specific steam turbine system, could be implemented in order to eval-uate stability or instability states, fatigue growth in the turbine blades, changes in the damping of the bearing system and perform necessary scheduled optimal and cost-effective maintenance strategies. Additionally, upon a series of scheduled experimental data collection, a permanent output-only vibration SHM system could be installed and even a proper dynamic balancing could be investigated and designed.